2017
DOI: 10.1111/cmi.12755
|View full text |Cite
|
Sign up to set email alerts
|

The midgut microbiota plays an essential role in sand fly vector competence forLeishmania major

Abstract: Summary For many arthropod vectors, the diverse bacteria and fungi that inhabit the gut can negatively impact pathogen colonization. Our attempts to exploit antibiotic treatment of colonized Phlebotomus duboscqi sand flies in order to improve their vector competency for Leishmania major resulted instead in flies that were refractory to the development of transmissible infections that was due to the inability of the parasite to differentiate into the infective, metacyclic stage. The parasite development defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 38 publications
2
62
0
Order By: Relevance
“…Considerable variation was observed in the composition of the microbiota within each group (Fig. S5 and S6); however, this variability was also detected between different groups of wt flies, consistent with our previous findings (34). In order to compare the quantities of bacteria colonizing the guts of rel mutant and wt flies during Leishmania infection, we performed 16S quantitative PCR (qPCR) experiments on pooled guts of females infected with L. major.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Considerable variation was observed in the composition of the microbiota within each group (Fig. S5 and S6); however, this variability was also detected between different groups of wt flies, consistent with our previous findings (34). In order to compare the quantities of bacteria colonizing the guts of rel mutant and wt flies during Leishmania infection, we performed 16S quantitative PCR (qPCR) experiments on pooled guts of females infected with L. major.…”
Section: Resultssupporting
confidence: 87%
“…The gut microbiota is modified in rel mutant flies. Previous studies reported that the sand fly gut microbiota plays a crucial role in its vector competence for Leishmania (33,34). With this in mind, we compared the relative abundances of bacterial species between small groups of wt and rel B heterozygous or homozygous mutants in the absence of Leishmania infection.…”
Section: Resultsmentioning
confidence: 99%
“…Phytocannabinoids from C. sativa exhibited antimicrobial activity against some bacteria and fungi (33). Since thriving gut microbiomes are crucial for the development of Leishmania infections in the sand fly gut (34,35), a microbicidal effect could harm Leishmania infections. Lastly, partially characterized compounds from C. sativa exhibited potent antileishmanial activity in vitro (36).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the gut bacteria of hematophagous vectors interact with parasites (like T. cruzi) occupying the same niche [2,23,24]. The microbiome can potentially impede parasite transmission through direct (competition for resources) and indirect (promoting immune response) interactions [25][26][27][28][29][30][31]. The most comprehensive background on hematophagous microbiomes has been derived from mosquitos, ticks, and tsetse flies (reviewed in [32]), whereas triatomine-bacteria associations remain neglected.…”
Section: Introductionmentioning
confidence: 99%